An investigation of patients with acute peripheral facial palsy with regard to Lyme disease - Kaygusuz, Irfan; Gödekmerdan, Ahmet; Karlidag, Turgut; Keleş, Erol; Yalçin, Sinasi; Tazegül, Ayça (My University, 2003)
OBJECTIVES: We investigated the role of Borrelia burgdorferi in the etiology of idiopathic acute peripheral facial palsy. PATIENTS AND METHODS: Nineteen patients (15 females, 4 males; mean age 38 years; range 14 to 61 years) with acute peripheral facial palsy were studied. Following routine otolaryngologic examination, all the patients underwent taste, Schirmer, and stapedial reflex tests to evaluate the level of the palsy. Laboratory examination included routine biochemistry analysis, serum C-reactive protein, rheumatoid factor, and erythrocyte sedimentation rate. Anti-Borrelia burgdorferi IgM and IgG antibodies were sought by ELISA in venous blood samples. RESULTS: Of the patient group, acute facial palsy was localized on the right in 12 patients (63.2%), and on the left in seven patients (36.8%). None of the patients had bilateral involvement. No IgM or IgG seropositivity for Borrelia burgdorferi was detected in the serum samples. CONCLUSION: In highly endemic areas, it may be helpful to detect or even to eliminate Lyme disease through screening of serum in patients with acute peripheral palsy.
Akut periferik fasyal paralizili olgularin Lyme hastaligi açisindan incelenmesi.
Keywords: Acute Disease; Adolescent; Adult; Antibodies, Bacterial; Borrelia burgdorferi Group; Facial Paralysis; Female; Humans; Immunoglobulin G; Immunoglobulin M; Lyme Disease; Male; Middle Aged; Turkey; bacterium antibody; immunoglobulin G; immunoglobulin M; acute disease; adolescent; adult; article; blood; Borrelia burgdorferi; facial nerve paralysis; female; human; immunology; isolation and purification; Lyme disease; male; middle aged; Turkey (republic)